The botany [of] the Antarctic voyage of H. M. discovery ships Erebus and Terror in the years 1839-1843, under the command of Captain Sir James Clark Ross. - Hooker, Joseph Dalton, Sir, 1817-1911.; Hooker, Joseph Dalton, Sir, 1817-1911. Flora Tasmaniae.; Hooker, Joseph Dalton, Sir, 1817-1911. Flora Novae-Zelandiae.; Hooker, Joseph Dalton, Sir, 1817-1911. Flora Antarctica.; Ross, James Clark, Sir, 1800-1862. (London, Reeve Brothers, Weinheim, J. Cramer; New York, Stechert-Hafner, 1847)
In this reprint, the plates from the three volumes are separately bound in one atlas. Plates 158-178 of volume one are bound after plate 198. v. 1. Flora Antarctica.--v. 2. Flora Novae-Zelandiae.--v. 3. Flora Tasmaniae. Mode of access: Internet.